2022
DOI: 10.24911/sjp.106-1623391582
|View full text |Cite
|
Sign up to set email alerts
|

Unusual sites of Rosai-Dorfman disease in children: 5 years' experience from tertiary care pediatric hemato-oncology center

Abstract: Rosai-Dorfman disease (RDD) is a rare histiocytic disorder, usually presenting with massive lymphadenopathy. The involvement of extra nodal sites, bone and nodal sites like mediastinum are rare. Clinical data of three cases of extra nodal RDD who were admitted in our Pediatric Hemato-oncology unit were analyzed in the last 5 years. The extra nodal RDD (maxillary sinus, nasal pharyngeal focus, and external auditory meatus) were diagnosed based on histopathology and positron emission tomography (PET) scan. They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The number of lymph nodes involved varied among the patients. Multiple lymph nodes were found in a total of 4 studies, involving 6 39 , 4 34 , 3 52 and 2 54 nodal sites while 7 studies 34,40,45,46,50,51,56 reported only one lymph node involvement. The types of lymph nodes affected (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of lymph nodes involved varied among the patients. Multiple lymph nodes were found in a total of 4 studies, involving 6 39 , 4 34 , 3 52 and 2 54 nodal sites while 7 studies 34,40,45,46,50,51,56 reported only one lymph node involvement. The types of lymph nodes affected (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4). Out of the 53 cases studied, 10 displayed unusual symptoms 24,25,33,34,36,43,44,52,53 . Specifically, the symptoms related to the eyes were observed in 5 studies 24,33,34,43,53 , while ear-related symptoms were observed in 3 studies 24,34,36 and paresthesia was seen only in 1 study 44 .…”
Section: Resultsmentioning
confidence: 99%